Analisis Fundamental Makro, Growth Opportunity Terhadap Nilai Perusahaan Dengan Struktur Kepemilikan, Kinerja Keuangan, Struktur Modal Sebagai Variabel Intervening Pada Perusahaan Manufaktur Sub Sektor Otomotif di Bursa Efek Indonesia (BEI) - Febrianti Novita; Hwihanus Hwihanus (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This research aims to determine the effectmacro fundamentals, growth opportunity on company value with ownership structure, financial performance, capital structure as intervening variables in automotive sub-sector manufacturing companies on the INDONESIAN STOCK EXCHANGE (BEI). The population in this research are automotive sub-sector companies listed on the INDONESIAN STOCK EXCHANGE (BEI) in 2019-2023. The sampling technique uses Purposive Sampling technique. The analysis tool in this research uses SmartPLS 4. The research results prove thatMacro Fundamentals have no significant effect on Company Value, Growth Opportunity has a significant effect on Company Value, Ownership Structure has a significant effect on Company Value, Financial Performance has no significant effect on Company Value, Capital Structure has a significant effect on Company Value.